EFEKTIVITAS ANALISIS BEBAN KERJA PEGAWAI (Universitas Riau, 2016)
The Effectiveness Analysis of the Workload of Employees. The purpose of this study was to determine the effectiveness of the analysis of the workload of employees Meranti Islands regency Regional Secretariat and the factors that hinder the effectiveness of the work load analysis. Samples were taken every employee contained in the work unit or section at the Regional Secretariat. The data collection is done with work sampling method is the observation of the activities performed by employees during working hours with a distance of observation time every ten minutes. After the data collected then analyzed by qualitative descriptive approach. The research found that the use of working time of employees is implemented and shared in productive activities, are not productive activities and private events can be concluded that each unit is still not optimal in performing routine administrative activities and duties and functions assigned. Barriers were found on the effectiveness of Secretariat staff workload analysis of Regency Meranti, namely expense budget workload analysis, information accuracy workload analysis, workload analysis and policy implementation in the managerial workload analysis.